Pitfalls of immigrant inclusion into the European welfare state - Martin Kahanec; Anna Myunghee Kim; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2011)
This paper's main purpose is to gauge immigrants' demand for social assistance and services and identify the key barriers to social and labor market inclusion of immigrants in the European Union. The data from an online primary survey of experts from organizations working on immigrant integration in the EU is analyzed using simple comparative statistical methods; the robustness of the results is tested by means of Logit and ordered Logit statistical models. We find that the general public in Europe has rather negative attitudes towards immigrants. Although the business community views immigrants somewhat less negatively, barriers to immigrant labor market inclusion identified include language and human capital gaps, a lack of recognition of foreign qualifications, discrimination, intransparent labor markets and institutional barriers such as legal restrictions for foreign citizens. Exclusion from higher education, housing and the services of the financial sector aggravate these barriers. Changes in the areas of salaried employment, education, social insurance, mobility and attitudes are seen as most desired by members of ethnic minorities. The current economic downturn is believed to have increased the importance of active inclusion policies, especially in the areas of employment and education. These results appear to be robust with respect to a number of characteristics of respondents and their organizations.
urn:nbn:de:101:1-201203016408
Keywords: J15; J71; J78; 330; ethnic minorities; migration; labor market integration; economic crisis; enlarged European Union; welfare state; Migranten; Ethnische Gruppe; Berufliche Integration; Soziale Integration; Sozialstaat; EU-Staaten